2013
DOI: 10.1159/000355743
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-Like Factor 15 Modulates Renal Interstitial Fibrosis by ERK/MAPK and JNK/MAPK Pathways Regulation

Abstract: Background/Aims: Renal interstitial fibrosis is a hallmark of progressive chronic kidney disease (CKD). Previous studies reported that kruppel-like factor 15 (KLF15) is an important regulator of cardiac fibrosis and could reduce the expression of extracellular matrix in mesangial cells. However, the role of this transcription factor in renal interstitial fibrosis has not been reported. Methods: In this study, we examined KLF15 expression in the remnant kidney of 5/6 nephrectomized rats 12 or 24 weeks after ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…CTGF, as a promising target for the treatment of renal fibrosis, seems to be an attractive target for anti-fibrotic therapy in kidney disease [23]. KLF15, an important transcription regulator, is greatly involved in regulating fibrosis [14, 15]. Wang et al [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTGF, as a promising target for the treatment of renal fibrosis, seems to be an attractive target for anti-fibrotic therapy in kidney disease [23]. KLF15, an important transcription regulator, is greatly involved in regulating fibrosis [14, 15]. Wang et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that KLF15, which is expressed in glomeruli and interstitium, is significantly down-regulated in the renal tissues of a 5/6 nephrectomised rat CKD model and that Klf15 -/- mice are more susceptible to renal fibrosis than wild-type mice [14]. Furthermore, our research group has reported the molecular mechanism of KLF15 in the regulation of TGF-β-induced renal fibrosis [15]. However, the role of KLF15 in Ang II-induced renal fibrosis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A newly developed angiotensin II receptor blocker, fimasartan, has beneficial effects in reducing renal oxidative stress, inflammation, and fibrosis by inhibition of the ERK1/2 and JNK pathways and upregulation of nuclear factor erythroid 2-related factor 2 signaling in mice with unilateral ureteral obstruction (UUO) and HK-2 cells [90]. Moreover, Kruppel-like factor 15 is a major factor in renal interstitial fibrosis, and can potentially prove to be an antifibrotic factor by regulating the ERK1/2 and JNK signaling pathways [91].…”
Section: Com/cpbmentioning
confidence: 99%
“…KLF15 is decreased in the renal interstitium of 5/6 nephrectomized rats and has been suggested to play an antifibrotic role, as in vitro studies demonstrate that KLF15 represses TGF-β1 signaling via ERK/ MAPK and JNK/MAPK pathways (16). Two studies have addressed the role of KLF15 in glomerular cells.…”
Section: Klfs and Mitochondriamentioning
confidence: 99%